Trade-Offs Between Hydraulic Efficiency and Safety in Cotton (Gossypium hirsutum L.) Stems Under Elevated CO2 and Salt Stress - Qing Zhao; Jinliang Chen; Jian Kang; Shaozhong Kang (Plants)
Plants respond to environmental changes by altering the anatomical structure of the xylem and its hydraulic properties. While numerous studies have explored the effects of individual environmental factors on crops, the combined interactions of these factors remain underexplored. As climate change intensifies, the occurrence of salt stress is becoming more frequent, alongside a rise in atmospheric CO2 concentration. This study aims to investigate the effects of elevated CO2 and salt stress on the hydraulic traits and xylem anatomical structures of cotton stems. Potted cotton plants were exposed to different CO2 concentrations (aC: 400 ppm; eC: 800 ppm) and salinity levels (aS: 0‰ soil salinity; eS: 6‰ soil salinity). The study found that under eC and eS conditions, a trade-off exists between hydraulic efficiency and safety in cotton stems, which may be partially attributed to xylem anatomical structures. Specifically, eS significantly reduced stem hydraulic conductivity under aC conditions and decreased vessel diameter but increased the proportion of small-diameter vessels and enhanced implosion resistance ((t/b)2), which strengthened the xylem’s resistance to salt-induced embolism. eC altered the response pattern of xylem hydraulic conductivity and embolism resistance to salt stress, with increased vessel diameter enhancing hydraulic conductivity but reducing xylem resistance to embolism. These findings enhance our comprehension of plant hydraulic adaptation under future climatic conditions and provide new insights into the trade-offs between xylem structure and function.